Environment‐Related Variation in the Human Mid‐Face. Issue 1 (January 2017) - Cui, Yaming; Leclercq, Sébastien
ABSTRACT: Previous studies that have examined mid‐facial morphology in geographically dispersed and genetically diverse groups of humans have shown a strong adaptation of the nasal part to extreme cold environments, which was not observed in non‐Arctic regions. However, it remains unclear whether different parts of the mid‐face area show independent adaptation to nonpolar climates, and if so, how this adaptation impacted the morphology. To address this question, we investigated potential associations between climatic variables and the mid‐facial shape in 14 populations, focusing on four aspects of the morphology: total shape, zygomatic, nasal and alveolar. The results show that when the genetic distance between populations is not considered, all aspects of the morphology are strongly correlated with all climatic variables. When the genetic distance is considered, significant correlations remain only for the zygomatic, and nasal parts with temperature, and for the nasal part and alveolar with sunshine exposure. A strong but probably artificial correlation of the alveolar with atmospheric pressure is also observed. Additionally, partial least square analyses indicate that tropical and subtropical environments are associated with smaller zygomatic and more triangular nose aperture compared to more temperate environments. These findings suggest that temperate and tropical climates have induced adaptation of zygomatic and nasal parts of the mid‐face in humans, and that this adaptation was probably driven by temperature and sunlight exposure conditions. Anat Rec, 300:238–250, 2017. © 2016 Wiley Periodicals, Inc.